Pengaruh Kompetensi PMIK Terhadap Kinerja Petugas Rekam Medis Di Rumah Sakit Angkatan Udara Dr. Esnawan Antariksa - Armila Astiyana Triadi; Dina Sonia; Puteri Fannya; Noor Yulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research was conducted with the aim of determining the influence of PMIK (Medical Recorder and Health Information) professional competence on the performance of medical record officers at the Dr. Air Force Hospital. Esnawan Antariksa. The research method used is quantitative with inferential analysis. The data collection techniques used were observation, interviews and questionnaires. The sampling technique used a total saturated sampling technique of 14 people. Obtained from 7 PMIK competency standard indicators (Noble Professionalism, Ethics and Legal, Introspection and Personal Development, Effective Communication, Health Data and Information Management, Clinical classification skills, Disease coding and other Health Problems as well as Clinical Procedures, Health Statistics Applications, Basic Epidemiology, and Biomedicine, Management of Medical Records Services and Health Information, there are still 2 indicators in the percentage that are not good, and in the 5 performance indicators of medical record officers (Quality of Work, Quantity of Work, Supervision, Attendance, Conservation) there are still 2 indicators in the percentage not good. It was found that 3 officers had a D-III RMIK education and 11 officers still had a high school education. Based on the results of the T test, it was found that the Sig. value was 275. It could be concluded that there was no influence of PMIK competency on the performance of medical records officers.